The Asylum Seeker Crisis and Europe Through the Lens of Human Security - Cikrikci, Tolga; Okur, Mehmet Akif (ANKARA UNIV EUROPEAN UNION RESEARCH CENTRE, 2021)
The great refugee movement that emerged after Arab Spring turned into an asylum seeker crisis for the European countries in 2015. The contradiction between the anti-immigrant policies and the human security discourse of the EU members is notable. In this study, the aforementioned contrast is discussed through the policies followed by the European countries against the crisis and anti-immigrant rhetoric. While doing this the visibility of the human security concept in EU documents and the anti-immigrant rhetoric that seems to be on the rise in parallel with the migration mobility have been tried to be put forward. It was concluded that the EU's immigration policies point to a structure that is designed outside of human security and leads to reverse feedback at the union-member levels.
Keywords: Human Security; Asylum Seeker Crisis; European Union Migration Policies; Xenophobia; Anti-immigrant Rhetoric; MIGRATION; IMMIGRANT; PARTIES; Area Studies